If we have the substitution for y, replace the y in the equation with -3
-3x-5(-3)=6
Multiply the -5 with the -3, and when you multiply a negative number with a negative it turns into a positive
-3x+15=6
Bring the 15 over to the other side of the equation to get the x number by itself like this —-> -3x=6-15 and when you cross over a number to the other side of the equation it’s positive or negative sign changes into the opposite
Now subtract
-3x=-9
Divide
-3x = -9
—— ——
-3 -3
And a negative number divided by a negative also makes the number a positive
X=3